Model-Based Magnetization Transfer Imaging Markers to Characterize Patients and Asymptomatic Gene Carriers in Huntington’s Disease - Wiest, Roland; Burgunder, Jean-Marc; Kiefer, Claus (Frontiers in Neurology, 2017)
Background and purpose: Huntington’s disease is a chronic progressive neurodegenerative disorder with a long presymptomatic period that opens a window for potential therapies aimed at neuroprotection. Neuroimaging offers the potential to monitor disease-related progression of the disease burden using model-based magnetization transfer imaging. Materials and Methods: We have conducted a cross-sectional study to stratify healthy age matched controls, pre-manifest and symptomatic Huntington’s disease patients (n=30) according to their macromolecular depositions in the caudate nucleus. We employed a binary spin-bath magnetization transfer method for a quantitative description of macromolecule deposits and interactions with their adjacent environment. Results: A region-of interest based fuzzy clustering analysis identified representative clusters for several stages of the disease course related to its progression: One cluster represented subjects with a high disease burden < 268 that encompassed all symptomatic Huntington’s disease patients and one pre-symptomatic gene-carrier. The next cluster represented the pre-symptomatic gene carriers with a very low disease burden > 230 and healthy controls. Three further clusters represented transition zones between both disease burden levels (230 – 268) consisting of pre-symptomatic carriers with disease burden values increasing with decreasing distance from the cluster that indicated low disease burden and healthy age matched controls. Conclusion: The proposed binary spin-bath magnetization transfer method offers the potential to monitor disease burden and progression in Huntington’s disease. The method may augment qualitative magnetization transfer techniques since it depicts tissue changes related to interactions between macromolecules and protons in disease specific brain regions that follow the neurodegenerative process.